2013
DOI: 10.4319/lo.2013.58.3.0867
|View full text |Cite
|
Sign up to set email alerts
|

Response of phytoplankton in an alpine lake to inputs of dissolved organic matter through nutrient enrichment and trophic forcing

Abstract: Inputs of terrestrially derived dissolved organic matter (DOM) are increasing in alpine lakes due to multiple drivers such as climate change, tree line advancement, and insect epidemics. A 21 d microcosm experiment investigated three potential mechanisms by which increased inputs of terrestrial DOM subsidies might affect phytoplankton density, growth, and species assemblage: (1) directly, by providing nutrients enhancing growth of select phytoplankton species (nutrient stimulation hypothesis); (2) indirectly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 53 publications
6
68
0
Order By: Relevance
“…Likewise increased algal biomass in the DOM Addition treatment in the N&P co-limited lake suggests that the N and P in DOM were largely bioavailable, with any P additions in particular likely facilitating the observed removal of nitrate in these treatments. The stimulation of algal biomass by DOM is consistent with other experiments that have demonstrated the availability of both N and P in DOM to phytoplankton in lakes (Berman and Chava 1999;Graneli et al 1999;Klug 2002;Kissman et al 2013) as well as those in estuarine and saline systems (Bradley et al 2010;Bronk et al 2010). It is possible that there are other components available in the DOM that are benefiting bacteria, which are then able to further breakdown or possibly mineralize DOM and increase the bioavailability of associated nutrients (Findlay and Sinsabaugh 1999).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Likewise increased algal biomass in the DOM Addition treatment in the N&P co-limited lake suggests that the N and P in DOM were largely bioavailable, with any P additions in particular likely facilitating the observed removal of nitrate in these treatments. The stimulation of algal biomass by DOM is consistent with other experiments that have demonstrated the availability of both N and P in DOM to phytoplankton in lakes (Berman and Chava 1999;Graneli et al 1999;Klug 2002;Kissman et al 2013) as well as those in estuarine and saline systems (Bradley et al 2010;Bronk et al 2010). It is possible that there are other components available in the DOM that are benefiting bacteria, which are then able to further breakdown or possibly mineralize DOM and increase the bioavailability of associated nutrients (Findlay and Sinsabaugh 1999).…”
Section: Discussionsupporting
confidence: 78%
“…Response to N addition is to the 40 lg NO 3 -N L -1 addition treatment, while the responses to DOM Shaded and DOM Addition are in the treatments without any N addition. Error bars indicate standard error Klug (2002) also found that chlorophytes as well as a species of Cryptomonas responded positively to DOM additions, while Kissman et al (2013) also found that the cell densities of several diatom taxa, including F. crotonensis, increased with a DOM addition. The responses of these different phytoplankton groups likely reflect multiple pathways by which increasing DOM can alter phytoplankton cell densities.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The close coupling between CDOM and nutrients further indicated that CDOM might be an important nutrient source for phytoplankton growth in lake water (Kowalczuk et al, 2010). For example, a 21 d microcosm experiment showed that the increasing inputs of terrestrial DOM caused an increase in biomass and a change in phytoplankton species assemblages (Kissman et al, 2013). Two mechanisms potentially explain how the nutrients from DOM stimulate phytoplankton growth.…”
Section: Coupling Between Cdom and Nutrient Concentrationsmentioning
confidence: 97%